2016
DOI: 10.1093/jxb/erw253
|View full text |Cite
|
Sign up to set email alerts
|

OlderThinopyrum intermedium(Poaceae) plants exhibit superior photosynthetic tolerance to cold stress and greater increases in two photosynthetic enzymes under freezing stress compared with young plants

Abstract: HighlightWe explore interactive effects of plant age and cold stress on photosynthetic rates and key photosynthetic enzymes in a herbaceous perennial in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
(55 reference statements)
2
23
0
1
Order By: Relevance
“…Significantly higher RuBisCO content has been shown for cold-adapted diatoms, chlorophytes, and land plants in comparison with their temperate counterparts (Devos et al, 1998;Yamori et al, 2005;Young et al, 2015;Jaikumar et al, 2016;Iñiguez et al, 2018). Moreover, the maximum RuBisCO carboxylation rate also depends on the binding of sugar phosphate inhibitors to the catalytic site and RuBisCO activase function.…”
Section: Temperature Dependence Of Rubisco Kinetic Traits: Adaptationmentioning
confidence: 99%
“…Significantly higher RuBisCO content has been shown for cold-adapted diatoms, chlorophytes, and land plants in comparison with their temperate counterparts (Devos et al, 1998;Yamori et al, 2005;Young et al, 2015;Jaikumar et al, 2016;Iñiguez et al, 2018). Moreover, the maximum RuBisCO carboxylation rate also depends on the binding of sugar phosphate inhibitors to the catalytic site and RuBisCO activase function.…”
Section: Temperature Dependence Of Rubisco Kinetic Traits: Adaptationmentioning
confidence: 99%
“…(2011), Han (), Jin et al (), Whitehead et al (), Xu and Zhou et al . (2011), Peguero‐Pina et al (, ,b), Tosens et al (,b, ), Varone et al (), Cano et al (), Martins et al (, ), Tomàs et al (, ), Battie‐Laclau et al (), Brito et al (), Hommel et al (), Théroux‐Rancourt et al (), Bazihina et al (), Benomar et al (), Cai et al (), Carriquí et al (, ,b), Kitao et al (), Lima‐Nieto et al (), Mizokami et al (), Shi et al (), Xiong et al (, , ), Dong et al (), Fini et al (), Huang et al (), Jaikumar et al (), Lu et al (), Medeiros et al (), Veromann‐Jürgenson et al (), Nadal et al () and Yang et al (). The two extreme lines of the boxplot ( whiskers ) show the 10 and 90% percentiles, the two boundaries of the box the 25 and 75% percentiles, and the centre thick line the median.…”
Section: Photosynthetic Capacity and Photosynthetic Efficiencies Alonunclassified
“…Cold acclimation and adaptation of photosynthesis may involve an enhancement of thermal energy dissipation, a reduction in effective photon absorption, metabolic adaptations that increase the antioxidant activity, and/or an increase in electron sink capacity. A higher electron sink capacity might be attained by an increased ratio of unsaturated fatty acids in thylakoid membranes, leading to the stabilization of transmembrane photosynthetic proteins (Falcone et al , ; Burgos et al , ), and by an increased concentration and activation state of CBC enzymes (Yamori et al , ), specially Rubisco (Savitch et al , ; Yamori et al , ; Jaikumar et al , ). Moreover, adaptations in RuBisCO kinetics through increased k cat c and carboxylation catalytic efficiency ( k cat c / K c ) have been reported in plants inhabiting cold ecosystems (Sage, ; Sáez et al , ).…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 99%
“…TPU limitation has been observed in warm-grown plants of the high-mountain grass Calamogrostis canadensis when the rate of photosynthesis is measured below 15°C, but this limitation was no longer observed after low-temperature acclimation (Kubien and Sage, 2004). TPU limitation has also been observed at high C i in the cold-tolerant grass Thinopyrum intermedium under cold stress (Jaikumar et al, 2016), and the authors suggested that it may be an underrated photosynthetic limitation in future scenarios of increased atmospheric CO 2 in cold environments. Nevertheless, more ecophysiological studies concerning the biochemical limitations of photosynthesis under native growth conditions, including the characterization of RuBisCO kinetics, are needed to corroborate the trends in biochemical adaptation of photosynthesis to extreme environments.…”
Section: Biochemical Limitationsmentioning
confidence: 99%